KEANEKARAGAMAN GASTROPODA DI PADANG LAMUN PERAIRAN PANTAI DESA RUTONG - Tetiwar, Welmina; Smith, Alwi; Liline, Sintje (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Gastropods are included in the mollusk phylum which is one of the non-fish biological resources that has quite high biodiversity. The gastropod community is an important component in the food chain in seagrass beds, where gastropods are detritus feeders. Methods: This research was conducted in seagrass beds in the waters of Rutong Village Beach in June-July 2022, using the quadrant linear transect method. The distance between transects is 25 meters with a total of 5 transect lines, each transect line has 10 plots and the distance between plots is 10 meters. Diversity of gastropods using index index formula, Evenness and Richness. Results: The results of measurements of environmental factors, namely temperature 29; pH 7.8; Salinity 34‰; DO 7.9 μg/l; Gastropod research results obtained 987 individuals consisting of 10 orders, 18 families, 22 general and 34 species. The index value of Diversity (H') is 1,394, the evenness index (E) is 0,395, and the wealth index is 4,786. Conclusion: Environmental factors in the seagrass bed of the coastal waters of Rutong Village are good for sustaining the life of gastropods; The types of gastropods found were 34 species; The Diversity Index (H') is moderate, the Evenness Index (E is low, and the Wealth Index (DMg) is moderate